2015
DOI: 10.4314/gjds.v11i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Inhibiting the Transformation of Subsistence Farming into Thriving Agri-business in Rural Uganda

Abstract: This study investigates the challenges involved in the development of agri-businesses in rural Uganda,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…With a weighted mean score of 3.5948, the findings show that market uncertainty is the most significant impediment to oyster mushroom commercialization. The findings are consistent with those of [ 98 ], who revealed that a lack of entrepreneurship skills, inadequate infrastructure, and a lack of markets prevent farmers from transitioning from subsistence farming to commercial farming. That is, the absence of the aforementioned factors impedes the commercialization of smallholder farming.…”
Section: Resultssupporting
confidence: 91%
“…With a weighted mean score of 3.5948, the findings show that market uncertainty is the most significant impediment to oyster mushroom commercialization. The findings are consistent with those of [ 98 ], who revealed that a lack of entrepreneurship skills, inadequate infrastructure, and a lack of markets prevent farmers from transitioning from subsistence farming to commercial farming. That is, the absence of the aforementioned factors impedes the commercialization of smallholder farming.…”
Section: Resultssupporting
confidence: 91%
“…The current condition of agriculture in Indonesia is generally still subsistence, which is characterized by a farmer's goal of his farming is only to meet the needs of his life and that of his family [4][5][6][7][8]. [8] stated that in Moldova, subsistence agriculture is still not oriented towards the commercialization of its production.…”
Section: Introductionmentioning
confidence: 99%